Development of a novel nontoxic vivid violet inorganic pigment – Mn3+-doped LaAlGe2O7. (January 2017) - Kim, Sun Woog; Saito, Yu; Hasegawa, Takuya; Toda, Kenji; Uematsu, Kazuyoshi; Sato, Mineo
Abstract: Novel nontoxic LaAl1- x Mn x Ge2 O7 (0.01 ≤ x ≤ 0.20) violet pigments were synthesized through a conventional solid-state reaction. The crystal structures, optical properties, and color properties of these pigments were investigated. The LaAl1- x Mn x Ge2 O7 (0.01 ≤ x ≤ 0.20) pigments prepared in the present study show excellent potential as environmentally friendly inorganic violet pigments. These pigments exhibit a strong optical absorption in the yellow-red light region due to the Mn 3+ d–d transitions, which is the origin of the violet color. Among the obtained LaAl1- x Mn x Ge2 O7 (0.01 ≤ x ≤ 0.20) pigments, LaAl0.90 Mn0.10 Ge2 O7 showed the most vivid violet color and the L *, a *, and b * values are 50.8, 18.0, and −29.7, respectively, values greater than those of a commercial cobalt violet pigment (Co3 (PO4 )2 ; L * = 46, a * = 33, b * = −32). Because the LaAl0.90 Mn0.10 Ge2 O7 pigment is composed of nontoxic elements, this pigment can be an effective alternative to currently used commercial violet pigments. Highlights: Novel LaAl1- x Mn x Ge2 O7 violet pigments were synthesized by a conventional solid-state reaction method. These pigments exhibit a strong optical absorption in the yellow-red light region. LaAl0.90 Mn0.10 Ge2 O7 showed the most vivid violet color. The L *, a *, and b * values of LaAl0.90 Mn0.10 Ge2 O7 were 50.8, 18.0, and −29.7, respectively. This pigment can be effective alternatives to commercial violet pigments.